Is free trade compatible with sustainable development. - MARKANDYA, Anil (1994)
Identifies three themes central to sustainable development: ensuring that future generations do not suffer as a result of present actions; that resources are used as efficiently as possible; and that development paths are not so inequitable as to push poor countries and poor individuals into environmentally degrading actions. Addresses two main questions: whether trade liberalisation conflicts with the goals of sustainable development; and, whether the instruments of economic and social policy that are required to achieve sustainable development result in a reduction in trade.